The Impact of Simulacra in Tere Liye’s Novel Hujan (a Study of Postmodernisme Based on Jean Baudrillard) - Elva Elva; Muhammad Rapi Tang (HUMAN: South Asian Journal of Social Studies, 2021)
This study aims to reveal the simulacra model in Tere Liye's Hujan novel, in terms of Jean Baudrilard's postmodernism. This research is descriptive qualitative in nature. The data in this study are in the form of words, phrases, sentences and paragraphs that contain the impact of simulacra. The source of data in this study is the novel Hujan by Tere Liye, published in Jakarta by Gramedia Pustaka Utama in 2016. The data in the study were analyzed using Jean Baudrillard's postmodernism theory. The data collection techniques used in this study were reading and note-taking techniques. Data analysis techniques are data reduction, data presentation, conclusion and verification. The results showed that the novel Hujan by Tere Liye found simulacra impact. The impact of the simulacra character dal of tere liye's rain novel is a symbolic consumption of items that started out as just a necessity and became a craving. Leads to a consumerism society because of the concept that brings many goods in one confined space. Visual garbage makes the flavor more interesting than the real information. Distension is a social distance because of the taste option. The loss of public space and the end of social life.Keywords: simulacra, impact, novel.